Pengembangan Digital Learning Kit untuk Membantu Meningkatkan Kompetensi Siswa dalam Perhitungan Biaya Produksi dan Penetapan Harga - Dwi Narullia; Setya Ayu Rahmawati; Satia Nur Maharani; Siti Mariyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
We must overcome students' low understanding of cost accounting courses with learning models that follow learning needs. Blended learning answers these problems, namely, using learning kits in modules, handouts, videos, and questions. This study aimed to determine the effectiveness of the use of the blended learning model on student learning outcomes in cost accounting courses at the State University of Malang. Based on the results of the tests carried out, it was found that there were differences in student learning outcomes that were equipped with a learning kit and students who did not equip. This indicates that students get a better understanding conceptually or in solving real problems. Learning models equipped with learning kits will improve student competence as reflected in learning outcomes.